Forming a Culture of Using the Needs of Students in the Flow of Information and the Sources that Delive It - Valijonovna, Raximova Gulbahor (Journal of Higher Education and Academic Advancement, 2024)
In this article, the importance of ensuring information security and achieving literacy is important in increasing the culture of using information media among students, and therefore, the issue of sorting out the necessary from the flow of information and the sources that deliver it, and forming a culture of use is highlighted.